Harassment of Female Workers: Implication and Impact - Lebsir, Chahrazed (Journal of Human Sciences, 2024)
Embodying our deep interest in women harassment and the importance of concerted efforts to contain it, this article attempts to unveil a phenomenon that has long been known to be silent and ignored in the work environment. The exacerbation of this problem and its multiple dimensions raise several problems to researchers and expand the scope of questions about the overlapping, intertwining and underlying factors behind it.In this regard, we sought to reveal the unequal relationship between men and women and the excessive male power that perpetuated all manifestations of violence, dwarfism, and harassment. This act actually results from masculine authority originating in society and extending to workplaces as professional authority, causing a role dysfunction within work communities.Using the findings of various humanities and social sciences in this field in terms of research around harassment is necessary to enact effective policies capable of providing protection for women in workplaces.